Design and analysis of mild steel mini truck body for increasing the payload capacity. (2021) - Satish, S.; John Alexis, S.; Bhuvendran, Arun; Shanmugam, Mohanraj; Baskar, S.; Shaisundaram, V.S.
Abstract: In India most of the small scale industries and traders would modify their vehicle body in order to maximize the load carrying capacity of the truck for economical reason. These alteration are done without proper design and analysis. In this work the vehicle body is designed to increase the pay load capacity of mini truck from 1.5 tons to 2 tons. The proposed model is analyzed for distributed load, line load and impact load due to cylindrical object. The impact analysis is done by assuming a set of cylinders weighing 1 tons dropped from 1 cm height. The vehicle body is modelled in CATIA and analyzed using ANSYS 16.2 FEA commercial software. The material chosen for analysis is mild steel. The strength of the body is assessed using deformation, stress and factor of safety value obtained from FEA analysis. The stress concentration is high at intersection point of body and chassis and also at top corner of the side channels and it is reduced by design modification. The final results shows that the proposed design is safe for the assumed.